2019
DOI: 10.1038/s41598-019-38673-w
|View full text |Cite
|
Sign up to set email alerts
|

Visual simulators replicate vision with multifocal lenses

Abstract: Adaptive optics (AO) visual simulators based on deformable mirrors, spatial light modulators or optotunable lenses are increasingly used to simulate vision through different multifocal lens designs. However, the correspondence of this simulation with that obtained through real intraocular lenses (IOLs) tested on the same eyes has not been, to our knowledge, demonstrated. We compare through-focus (TF) optical and visual quality produced by real multifocal IOLs (M-IOLs) -bifocal refractive and trifocal diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
0
42
0
3
Order By: Relevance
“…The procedure, and the resultant SimVis simulation, has already been validated in intraocular lenses with sophisticated surface geometries (zonal refractive or diffractive). 20 Consequently, novel MCLs could be visually simulated with SimVis, even before they are manufactured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure, and the resultant SimVis simulation, has already been validated in intraocular lenses with sophisticated surface geometries (zonal refractive or diffractive). 20 Consequently, novel MCLs could be visually simulated with SimVis, even before they are manufactured.…”
Section: Discussionmentioning
confidence: 99%
“…These features have allowed for the concept to be translated into a binocular, wearable clinical device (SimVis Gekko). Previous studies have proven the capability of the SimVis technology to replicate vision with real refractive segmented IOLs and trifocal diffractive IOLs 20 and a high correspondence between preoperative vision with SimVis Gekko and postoperative vision with the real implanted multifocal IOL. 26 The ability of SimVis technology to allow subjects to noninvasively experience multifocal vision is highly useful before intraocular lens implantation, given that a lack of tolerance to implanted multifocal IOLs may require surgical explantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike theoretical models, experimental visual simulators incorporate both ocular optics and neural factors, showing visual testing of different multifocal patterns and offering patients a direct visual experience before fitting a specific multifocal contact lens design. ese simulators are based on adaptive optics elements (deformable mirrors or spatial light modulators [51][52][53]) or temporal multiplexing (e.g., SimVis technology [54][55][56]) and work by projecting the theoretical multifocal pattern design onto the patient´s pupil plane, allowing us to evaluate the effect of different distance-near pupillary distribution and to test directly the visual performance. Recent studies have demonstrated that the through-focus visual performance with the same multifocal pattern varied across individuals, indicating that the specific performance of the design is highly patient-specific since not all patients tolerate well the out-of-focus image components in simultaneous vision [55].…”
Section: Evaluation Of the Visual Performance In Simultaneousmentioning
confidence: 99%
“…An alternative simulation of multifocal patterns is that used by the SimVis technology (https://www.2eyesvision.c om/es/simvis/), operating under the principle of temporal multiplexing of optotunable lenses, 10 which has been used to mimic commercial intraocular lenses, with several advantages over previous simulators: it is see-through, allows a wide field of view, and is very compact (a current commercial instrument based on this technology is binocular and wearable). In a recent study 11 an optotunable lens (SimVis) and a cuvette with a real segmented intraocular lens were placed in pupil conjugate planes in the testing channel of AOII. Through-focus visual acuity was measured with either simulator (SimVis, SLM or real lens in 2ANG stands for bifocal angularly segmented intraocular lens (IOL); 2RAD stands for bifocal radially segmented IOL; 3ANG stands for a 3-zone angularly segmented IOL; 3RAD stands for 3-zone radially segmented IOL; 4ANG stands for a 4-zone angularly segmented IOL; 4RAD stands for 4-zone radially segmented IOL; Bi-R stands for bifocal refractive IOL and Tri-D stands for trifocal diffractive IOL.…”
Section: Chromatic Aberrationmentioning
confidence: 99%